A8.1 Alarmins S100A8/A9 Cause Osteophyte Formation in Experimental Osteoarthritis with High Synovial Involvement. (25th February 2013) - Schelbergen, Rik FP; Blom, AB; Munter, W de; Sloetjes, A; Vogl, T; Roth, J; Berg, WB van den; Lent, PLEM van
Abstract : Background and Objectives: Osteophyte formation is an important hallmark of osteoarthritis (OA) causing limited joint movement and pain. There is increasing belief that synovial activation contributes to OA pathology. As shown recently in our lab, alarmins S100A8 and S100A9 (major products of synovial macrophages) are involved in cartilage degradation and synovial activation during human and murine OA. In the current study, we explored the involvement of S100A8/A9 in osteophyte formation in experimental OA. Methods: Experimental OA was elicited in C57Bl/6 (WT) mice and S100A9 -/- mice, which also lack functional S100A8. Collagenase induced OA (CIOA) was induced by two times intra-articular injection of 1U collagenase, DMM was induced by transsection of the medial anterior meniscotibial ligament leading to destabilisation of the medial meniscus (DMM). Osteophyte size was assessed by a blind observer using Leica Application Suite (LAS) imaging software. Chondrogenesis was induced by bringing human foetal mesenchymal stem cells (MSCs) in pellet and stimulating for 5 days with BMP-2 and TGFβ1, with or without human recombinant S100A8. Proteoglycan content was quantified using the LAS imaging software on SafO stained sections. Results: First, we measured osteophyte size in S100A9 -/- mice at day 42 of CIOA. Synovial activation is high in CIOA and this is significantly reduced in S100A9 -/- mice. Osteophyte size was dramatically reduced in the S100A9 -/- compared to WT in the medial collateral ligament (92.5% reduction) but also significantly at the medial side of both tibia and femur (68.2% and 64.6% reduction) (n = 10). One explanation for the reduced osteophyte size in S100A9 -/- mice may be a direct effect of S100-proteins on chondrogenesis. To investigate this, we stimulated MSCs in pellet culture with BMP-2 and TGFβ1, supplemented with 1 and 5 µg/ml S100A8. Proteoglycan deposition as measured by redness in SafO staining was increased 27% and 71% respectively, indicating that S100A8 stimulates chondrogenesis. Finally, we determined osteophyte size in the DMM model, in which synovial involvement is very low. At day 56, we observed no significant differences in osteophyte size between the S100A9 -/- and WT at the medial femur and tibia (105% and 136% of WT, n = 8). This confirms the importance of the synovium in the S100-effect on osteophyte development. Conclusions: S100A8/S100A9 play a crucial role in osteophyte formation in an OA model that shows clear synovial involvement, probably by stimulating chondrogenesis. Considering also the deleterious effect of S100A8/A9 on joint destruction in OA, targeting these alarmins during OA may be very promising.